Theology and Ecology across the Disciplines On Care for Our Common Home (Volume 5) - Deane-Drummond, Celia; Artinian-Kaiser, Rebecca (2018)
The threat of ecological collapse is increasingly becoming a reality for the world's populations, both human and nonhuman; addressing this global challenge requires enormous cultural creativity and demands a diversity of perspectives, especially from the humanities. Theology and Ecology Across the Disciplines draws from a variety of academic disciplines and positions in order to explore the role and nature of environmental responsibility, especially where such themes intersect with religious or theological viewpoints. Covering disciplines such as history, philosophy, literature, politics, peace studies, economics, women's studies, and the ecological sciences as well as systematic and moral theology, the contributors emphasize how these positions have begun to develop distinct perspectives on urgent ecological issues, as well as pointing toward specific practices at the local and international level. This volume provides a multidisciplinary point of departure for urgent conversations on environmental responsibility that resist simplistic solutions. Rather, the contributors highlight the complex nature of modern ecology, and suggest creative ways forward in the situation of an apparently intractable global problem.